Three romances of Eastern conquest - Greene, Robert, 1558-1592; Kyd, Thomas, 1558-1594; Heywood, Thomas, approximately 1574-1641 (Revels plays companion library., 2018)
This volume brings together three little-known works by key playwrights from the late sixteenth-century golden age of English drama. All three convey the public theatre's fascination with travel and adventure through the popular genre of heroic romance, while reflecting the contemporaries' wide range of responses to cross-cultural contacts with the Muslim East and the Mediterranean challenges posed by the Ottoman empire.0The volume presents the first modern-spelling editions of the three plays, with extensive annotations catering for specialised scholars while also making the texts accessible to students and theatre-goers. A detailed introduction discusses issues of authorship, dates and sources, and sets the plays in their historical and cultural contexts, offering exciting insights on Elizabethan performance strategies, printing practices, and the circulation of knowledge and stereotypes related to ethnic and religious difference.